(untitled) (TAJ: Journal of Teachers Association, 2018)
Stroke is one of the commonest causes of death and disability in the world. Hypertension is the greatest treatable risk factor for both ischernic and hemorrhagic stroke. This study was carried out in Rajshahi Medical College Hospital to observe the incidence of stroke among hypertensive patients and to compare the occurrence of stroke among patients who were taking anti-hypertensive drugs regularly and those who were taking irregularly. Hundred stroke patients with hypertension were selected randomly. Ischemic stroke 66% and hemorrhagic stroke 34% was observed. Majority (64%) of hypertensive patient was treated irregularly and only 36% patients were treated regularly with drugs. Incidence of ischemic (66.6%) and hemorrhagic (58.8%) stroke was increased in irregularly antihypertensive treatment patients. TAJ 2014; 27(2): 30-32